Embedding learning development; a model for collaborative practice - Laura Minogue (Association for Learning Development in Higher Education (ALDinHE), 2018)
In 2016, the Learning Development Team at St Mary’s University was awarded a prize for teaching excellence for its report on 'the collaborative delivery of embedded academic skills development programmes within subject modules’. The report detailed the planning and delivery of embedded activities across Schools in which academic skills were tailored to subject specific module content. The success of the report resulted in long-term investment in the Learning Development Team and positioned embedded academic learning as an integral part of the university’s corporate plan. This paper presents the results of a small-scale research study to evaluate an embedded academic skills module in Criminology and Sociology delivered at Level 4. The impact of this embedded module has been measured through semi-structured interviews with students, the subject lecturer and learning development lecturer. The final self-evaluation assessment was also analysed to understand more fully how students had developed over the course of the module. Results clearly demonstrate that embedding academic skills into the Criminology and Sociology programme had an impact on student confidence, belonging and retention. The outcome is an 'impact-tested' accredited skills module that can be adapted and used by other learning development teams.